Sequence of a cysteine-rich galactose-specific lectin of Entamoeba histolytica. - Mann, B J (1991)
Entamoeba histolytica trophozoites adhere to human colonic mucins and epithelial cells by a cell surface galactose-specific lectin. This lectin, which is composed of two subunits linked by disulfide bonds, has been shown to be a protective antigen in an animal model of amebiasis. We have determined the sequence of the mature form of the 170-kDa heavy subunit from cDNA clones and PCR-amplified fragments. The heavy subunit sequence consisted of a putative extracellular domain containing 1209 amino acids with 16 potential sites for N-linked glycosylation, a 26-amino acid hydrophobic region, and a 41-amino acid cytoplasmic tail. The presence of N-linked oligosaccharides was confirmed by culturing amebae with tunicamycin, which resulted in a decrease in the heavy subunit molecular mass to 160 kDa and a loss of lectin activity. The extracellular domain was remarkable for an extensive cysteine-rich domain that shared identify with similar regions of several other cell surface proteins and appeared to confer protease resistance to the subunit.